Community Empowerment Through Probiotic Production and Fish Feed Production Based on Local Materials in Gapoktan Mekar Mulyo, Sukun District, Malang City - Ganjar Adhywirwan Sutarjo; David Hermawan; Rahmad Pulung Sudibyo (Jurnal Dedikasi, 2020)
Increasing the local materials' utilization through community participation in freshwater fish farming is one of the keys to realizing family-based food independence. It can be done by utilizing narrow land, utilizing local raw materials that can be used as ingredients for handmade fish feed, preventing pests and diseases, and improving the aquatic environment's quality. Those steps need to get the attention of various parties through an appropriate technology approach. One of the areas for developing freshwater fish farming in Malang is the Sukun sub-district. The fish farmer group association called "Gapoktan" in the sukun sub-district that carries out fisheries activities is the "Mekar mulyo" Gapoktan. Gapoktan Mekar Mulyo was formed in 2014 with the chairman, Mr. Rahmad, located in Gadang village, Sukun sub-district. There are four groups: one mina weling fish cultivator group, two farmer groups, namely blossom sari, advanced farmers, and one mulyo farmer group. The number of group members is 55 people. Internal community service activities for Gapoktan "Mekar Mulyo" fish farmers in Gadang village, Sukun District, Malang City aim to increase knowledge and skills on the application of acceptable fish farming methods (CBIB), to improve partners' skills in producing fish feed based on indigenous raw materials, and to increase the skills and knowledge of partners in environmental management based on herbal plants. The methods used in the fisheries team's internal community service program where training and mentoring on acceptable fish farming methods (CBIB), independent fish feed production, and probiotic propagation based on local raw materials. The internal community service activities results are as follows: partners can implement an intensive cultivation system in freshwater fish cultivation activities based on acceptable fish farming practices (CBIB). The program partners have succeeded in producing independent fish feed in fermentation, increasing probiotics manufactured from local raw materials, and partners can implement sustainable water quality monitoring. This evaluation is in line with the increase in fish production data during the activity.